Adaptive filtering in ECG monitoring of the fetal heart rate - Frank, T H; Blaumanis, O R; Gibbs, R K; Wells, R K (Journal of electrocardiology, 1987)
There has long been an interest in noninvasively monitoring the fetal electrocardiogram (ECG). In the past twenty years a clinical need has developed to monitor the instantaneous fetal heart rate (FHR) and changes in the heart rate from one beat to the next, i.e., beat-to-beat FHR variability as well as an interest in understanding the development of cardiac arrhythmias. The purpose of this paper is to present initial results obtained from an Electrocardiographic Adaptive Processor (EAP) to noninvasively monitor in real-time continuous tracings of the fetal ECG, FHR, and FHR variability. Twenty-five sets of noninvasive fetal ECG data were collected from pregnant subjects during the third trimester of pregnancy using maternal abdominal paste-on electrodes. The fetal QRS amplitude and shape varied from 5 to 30 microvolts with fetal position, gestational age, and relative electrode configuration. Results have been obtained in three specific areas: 1) The development and initial testing of a microprocessor based Electrocardiographic Adaptive Processor (EAP) implemented as an FHR monitor has been completed. The EAP has been implemented to adaptively cancel, in real-time, the maternal ECG component from maternal abdominal ECG leads to provide a continuous tracing of the fetal ECG complex, or FHR and FHR variability. 2) Maternal and thoracic ECG data stored on computer disk were used to test the adaptive techniques to cancel the strong interfering maternal ECG. Studies continue to effectively reduce background electromyographic (EMG) noise. 3) Tracings of the fetal QRS complex, instantaneous FHR, and short term FHR variability have been obtained in real-time.